2014
DOI: 10.1021/jp5002463
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Electrolytes: Revealing the Mechanisms of Li-Ion Conduction in Tetragonal and Cubic LLZO by First-Principles Calculations

Abstract: In this study, we applied first-principles-based calculations, such as ab-initio molecular dynamics simulation, metadynamics, and nudged-elastic band calculations, to successfully identify the mechanisms responsible for the considerable difference in ionic conductivity between the tetragonal and the cubic phases of LLZO (Li 7 La 3 Zr 2 O 12 )a promising candidate for use as a highly Li-ion conductive solid-state electrolyte in Li-based batteries. Whereas in tetragonal LLZO the motion of Li ions is of fully co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
217
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(251 citation statements)
references
References 59 publications
24
217
2
Order By: Relevance
“…These results are consistent with other simulation studies. 25,26,29 In the case of Ga atoms (for x = 0.30), their MSD starts to increase at 1200 K (Figure 5c). This onset temperature for Ga ion diffusion does not vary with respect to Ga content (see Figure S4 in the Supporting Information).…”
Section: +mentioning
confidence: 98%
See 2 more Smart Citations
“…These results are consistent with other simulation studies. 25,26,29 In the case of Ga atoms (for x = 0.30), their MSD starts to increase at 1200 K (Figure 5c). This onset temperature for Ga ion diffusion does not vary with respect to Ga content (see Figure S4 in the Supporting Information).…”
Section: +mentioning
confidence: 98%
“…The trajectory of the x = 0 case is in strong agreement with a recent analysis of neutron powder diffraction data 62 as well as several simulation studies. [25][26][27]29 To make a clear comparison with the x = 0.30 case, we chose an appropriate slab section to expose the full 2D plane view of Li pathway connectivity, such as plane (3 6 4), which is shown in blue in Figure 10a and 10c. As can be seen, pathway features such as junctions formed by Td sites (LiO 4 ) and density lobes formed by Oh sites (LiO 6 ) can be observed in detail (Figure 10b, d).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jalem et al 24 identified a concerted Li + migration mechanism in cubic LLZO via AIMD simulations. Meier et al 108 compared the differences in Li + diffusion in tetragonal and cubic phases using a similar technique. In tetragonal LLZO, the Li + motion is of a fully synchronous collective nature requiring higher activation energy, whereas in cubic LLZO, because of the existence of unoccupied Li sites, the asynchronous collective motion of Li + caused by single-ion jumps leads to lower activation energy.…”
Section: Llzo Garnetmentioning
confidence: 99%
“…Although not reported yet, this process should be correlated to electromigration mitigated effects such as carbon insertion [17], Frenkel pair nucleation [26] or oxygen gradient in UO 2+x [27]. Moreover the extremely fast cooling rate used in SPS sintering could have quenched the system into a metastable state with highly disordered ionic distribution, favoring high Li mobility [5,25,[28][29].…”
mentioning
confidence: 96%